Self-initiated humour protocol: a pilot study with an AI agent - Edalat, Abbas; Hu, Ruoyu; Patel, Zeena; Polydorou, Neophytos; Ryan, Frank; Nicholls, Dasha (Frontiers in Digital Health, 2025)
IntroductionNon-hostile humour and laughter have been known for therapeutic benefits in an individual’s mental health and wellbeing. To this end, we evaluated the Self-Initiated Humour Protocol (SIHP), a new type of self-administrable laughter intervention that utilises spontaneous and self-induced laughter. Rooted in the core principles of the Self-Attachment Technique—in which an individual creates an affectional bond with their childhood self as represented by their childhood photo or personalised childhood avatar—SIHP provides an algorithmic framework for individuals to learn to laugh in a non-hostile manner and develop a sense of humour in all possible life contexts. This allows SIHP to be self-administered by interacting with an AI agent.MethodsAn 8-week intervention was conducted with N = 27 adult participants. Exclusion criteria: severe depression or anxiety (PHQ-9 and GAD-7 scores above 15). Participants’ measurements were collected in the areas of wellbeing, use of different humour styles, emotional self-regulation, self-compassion and psychological capital, and analysed to understand any changes over time. Measurements were taken immediately before, after the intervention, and at the 3-month follow-up. Throughout the intervention, participants were required to practise SIHP 20 min a day with the aid of an emotionally intelligent chatbot and their personalised child avatar in virtual reality (VR).ResultsAnalysis of results at the 3-month follow-up showed significant improvements in the primary outcome of wellbeing with large effect size (r=0.92), as well as a range of secondary outcomes with large effect sizes, self-compassion (r=0.93), use of self-enhancing humour (d=0.80), and emotion regulation (d=0.87); the results also showed improvement to participant’s psychological capital with moderate effect size (d=0.56).DiscussionThis study shows the potential for the practice of SIHP as supported by an emotionally intelligent chatbot and personalised child avatar to have medium-term positive effects, which should be validated through future randomised trials.